Current and future research on the association between gut microbiota and breast cancer - Liu, Kuan; Jia, Nan; Shi, Hongyun; Ran, Yuge (Frontiers in Microbiology, 2023)
Breast cancer (BC) is a prevalent malignancy. There exists a strong association between gut microbiota and the development of breast cancer.The gut microbiota composition in individuals with breast cancer significantly differs from that in their healthy counterparts. Furthermore, the distribution of gut microbiota varies significantly among individuals with different types of breast cancer. The gut microbiota can impact breast cancer through metabolite secretion, the gut-mammary axis, and other pathways. Modulating the gut microbiota can serve as a very promising potential therapeutic strategy in the treatment of breast cancer. This paper will summarize existing research, focusing on the relationship between intestinal microbiota and breast cancer. At the same time, the project will also analyze the application value of intestinal microorganisms in breast cancer intervention work, so as to provide a reference for the further development of breast cancer prevention and treatment work.